Respon Genotipe Padi Lokal terhadap Cekaman Rendaman di Pembibitan - Sri Romaito Dalimunthe (Proceedings Series on Physical & Formal Sciences, 2021)
Uncertain climate change impacts the difficulty of predicting the intensity of floods that hit rice fields in flood-prone areas, both the duration of the submerged plants and the height of the water surface. In order to evaluate the tolerance level and response of several local rice genotypes to submersion stress in the vegetative phase, 50 rice genotypes were screened (47 North Sumatran local varieties, 3 VUB), using special ponds to simulate flooding or inundation stress. The study used a separate plot design with three replications; the main plot was three immersion models, namely full immersion, partial soaking, and not soaking, and subplots of 50 rice genotypes. The immersion treatment was defined as a different growing environment. The results showed that in the fully submerged treatment, the recovery capacity of local rice plants only ranged from 0-20%. The new, improved varieties tested were Inpari 4 (susceptible), Inpari 3, 10, Ciherang, Inpara 2 (very susceptible), Inpari 30, FR13A (very tolerant). Submersion tolerant genotypes had a slight increase in plant height after being fully submerged. The chlorophyll content in the leaves decreased immediately after the soaking stress period (14 DAP) in all rice genotypes. The local rice genotypes tested were very susceptible to immersion; the new superior variety Inpari 4 was categorized as susceptible, while Inpari 30 and FR13A were very tolerant.